Investor Herding Behavior in Extreme Conditions During Covid-19: Study On Indonesian Stock Market - Sadewo, Rizal Abdul Jabbar; Cahyaningdyah, Dwi (Universitas Negeri Semarang, 2022)
Herding behavior as a financial behavior bias is defined as the tendency of investors to imitate other decisions without prudent consideration. The aim of this paper is to analyze the effect of investor herding behavior in extreme market conditions during Covid-19 pandemic on the Indonesia Stock Market. The data used in this study is cross-sectional absolute deviation of stock return and market return. The samples included in the research criteria were 80 companies. The samples were analyzed using CCK2000 method and robustness test using Tan 2008 method with help of the Eviews 12 application. The empirical results of this study found the effect of investor herding behavior during extreme conditions of Covid-19 pandemic (general model) and during bearish market period. Meanwhile, no effect of herding behavior was found during bullish market period on the Indonesian Stock Market. Two of the four robustness test models are robust.